Diagnostic clues in spontaneous intracranial hemorrhage in babies - Julius July; Eka Julianta Wahjoepramono; Beny Atmadja Wirjomartani (Paediatrica Indonesiana, 2008)
Background There has been increasing number of babies detectedwith SIH. In regard to find diagnostic clues for the first-rate babieswho really needs CT scan and referral, simple observation to lookat certain clinical and laboratory findings is needed.Objective To identify diagnostic clues associated with spontaneousintracranial hemorrhage (SIH) in babies.Methods Retrospective observation was carried out among ba-bies with SIH within the last two and a half years. Patients wereexcluded if there was an obvious cause of SIH such as trauma orany underlying disease such as hemophilia. Variables that wereobserved were patient's age, seizure, decreased level of conscious-ness, tensed fontanel, neurological deficits, vomitting, fever(T > 3 7 .SOC), anemia, jaundice, PT and aPTT. All data weredescriptively evaluated.Results There were 53 babies with SIH (31 baby boys, 22 babygirls), forty eight of which (91%) were less than 3 months old.Of those, 50 patients (94%) had seizure as the leading clinicalpresentation, 44 patients (83%) had decreased level of conscious-ness, and 39 patients (74%) had tensed fontanel. PT and aPTTwere prolonged in 39 (74%) cases. The most common lesion wassubdural hematoma (38 cases/72%). Forty-three babies (81 o/o)required neurosurgical intervention. Overall mortality rate was22%.Conclusion Babies with seizure, decreased level of consciousness,tensed fontanel, and prolonged PT and aPTT should be consideredto harbor SIH. They need a CT scan and referral, particularlythose less than three months old. The prognosis is unfavorable,thus early recognition and treatment is needed